PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE LEARNINGTIPE LEARNING TOGETHER (LT) TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI - Elsa Sulfiana Sari; Tiara Anggia Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The problems in this research are still many students who have not reached the value of KKM or not yet complete the learning result of economy Class XI IPS 3 even semester SMA Negeri 1 Kotagajah academic year 2017/2018 and has not played an active role in the process of learning in the classroom, used by teachers is still not appropriate to optimize student learning outcomes class XI IPS 3 even semester SMA Negeri 1 Kotagajah academic year 2017/2018. So the formulation of the problem is